Unveils key proteins in Xinjiang goat muscle linked to post-mortem meat quality: A TMT-based proteomic analysis - Duoduo Zhang; Hong Yu; Minghui Gu; Shiquan Zhang; Xiaolin Ma; Wei Zhang; Yanlei Zhu; Majida Al-Wraikat; Mohamed Aamer Abubaker; Rui Zhang; Yongfeng Liu (Food Chemistry: X)
An extensive proteomic analysis utilizing the tandem mass tag (TMT) method was conducted to investigate the changes in protein expression in the longissimus dorsi muscle of Xinjiang goats over various post-mortem intervals: immediately after death within 0 h, 12 h, 24 h and 48 h. The investigation carefully identified around 108 proteins that showed significant changes in expression during these intervals. Among these proteins, six were highlighted for their crucial roles in muscle growth and differentiation of muscle fibers post-mortem. These proteins, namely COL12A1, MRPL46, CTNNB1, MYH1, CAPZA1, and MYL9, have a direct effect on the meat's quality attributes, such as tenderness and color. Further discuss observed a progressive increase in the expression of proteins linked with oxidative metabolism (MSRB2, ENOX1, LOC102170282, GSTM1, and AOC3) as the post-mortem aging period extended, particularly between 24 h to 48 h. These proteins are instrumental in defining the color and flavor profiles of goat meat, underscoring the importance of precise processing and storage conditions to preserve meat quality during the critical aging phase. This enhanced understanding of protein expression dynamics offers significant implications for optimizing meat quality and provides a scientific basis for post-mortem handling practices in the goat meat industry.